Research on a visualized real-time monitoring system for the slurry chamber of a slurry shield. Issue 5 (October 2020) - Li, Dongli; Pu, Xiaobo; Qi, Baowei; Ma, Lin
Abstract: In this study, a visualized real-time monitoring system was established to monitor the working conditions of the slurry chamber and collect rotation situations of the cutter head, wear conditions of the disc cutters, image information of the excavated strata and flow characteristics of the slurry. The operating condition of the front-end equipment is shown on the upper computer, and the signal collected by the camera is transmitted to the video acquisition system in real-time. Hence, this paper presents solutions to the system with an emphasis on the system structure, hardware, and software design, and verification. The system verification was conducted through a field test in a project site, where the system could reliably monitor the slurry chamber.